Study on the Relationship between Mechanical Properties and Mesostructure of Microbial Cemented Sand Bodies - Yue Yan; Yang Tang; Guobin Xu; Jijian Lian; Dengfeng Fu (Advances in Materials Science and Engineering)
Microbial-induced calcite precipitation (MICP) is a novel ground improvement method to effectively increase the strength of sandy soil. However, the relationship between the compressive strength of cemented sand and mesostructure of the cemented structure has not been addressed adequately. In this paper, a suite of microbial cementing experiments were conducted, considering multiple parameters controllable in testing. Twenty-two cementing columns were examined by uniaxial compressive strength (UCS) tests to explore the response of variations in compressive strength. The correlation of compressive strength with mesostructure of cemented samples was investigated using the X-ray computed tomography (XCT) method. Three main influential factors—the uniform spatial distribution, increasing contents, and increasing size of the crystals—were found to contribute positively to the strength behavior. Under relatively uniform spatial distribution, increasing the contents of crystals facilitated the initial construction of “spatial network” structure, and further stacks of calcium carbonate crystals promote the complete construction of the “spatial network” structure, and thus helped to increase compressive strength. The spatial distribution curves of crystals are in good agreement with the destructive characteristic curves of structures.